Formulation and nebuJization of fluticasone propiondte-loaded CrossMark lipid nanocarriers - Umerska, Celia; MOUZOUVI, Rosmonde; BIGOT, KOFFI ANDRÉ; Saulnier, Patrick (My University, 2015)
ln I1J:ed nu tic.lsone pro lon,lte ( r) is fi ('<1 prcscnlJe 15 a fi r sr -llIle therapy for lhe enec live ma ndgemenl of pulmonary dls~dses such as "sthma. As nanocarriers offe mJny ddvdntdges over otl1er drug delivery systems. this stuoy investig,l'::! ttle sllir.lbility of lipid nan(l[.'psules (LNCs) dS a carrier for nuticasone propionare.examining lhe drug-relJtcd factors that should be consitJered in the formulation design and the bellaviuur of LNCs \Nith different compositions and propenies sllspended within aerosol drapiers uneler rhe relalively hostile candirions of nebuhzation. By adiusting the fUll1luldtion conditions, particlilarly the flJnocarrier composition. Fr was e fkiently encapslli,HCcJ v!irhin tlle LNCs with a yielcl ofllp to 97';{,. "nel a c(Jncentr'arion comparable ra commercially available p~iJJrations was achieved. iI1oreover. resting The solubility of rhe drug in ail and W,l1er and deterlll'llIng the oll/wi\tcr [ldl'rlr(on coefli ienl proveel ro be "se:ul when assesslng the enCl[lSl<!.Jlrorl of lhe Fr in the LNC formulation. Nebulizarior. clrd not cause the Fr to kak from tlle formulaTion. anel no phase separation WdS observeel ,1 ftcr nebu lizalion. LNCs wirh a dia metcl of 100 nm con taini ng a sma Ile r amou nr of SLl! facta nt and a larger amounr of ail provideel a better Fr-Ioadng c.lpaciry and beTter stabiliry during nebultzarion than 30 or 60 nm LNCs.
Keywords: LIPID